Risk Factors and Genetic Biomarkers of Multiple Primary Cancers in Esophageal Cancer Patients - Yang, Pei-Wen; Lin, Mei-Chun; Huang, Pei-Ming; Wang, Cheng-Ping; Chen, Tseng-Cheng; Chen, Chun-Nan; Tsai, Mong-Hsun; Cheng, Jason Chia-Hsien; Chuang, Eric Y.; Hsieh, Min-Shu; Lou, Pei-Jen; Lee, Jang-Ming (Frontiers in Oncology, 2021)
Esophageal cancer (EC) is a deadly cancer that frequently develops multiple primary cancers (MPCs). However, the risk biomarkers of MPC in EC have hardly been investigated. We retrospectively enrolled 920 subjects with primary EC and analyzed the possible risk factors as well as MPC single-nucleotide polymorphisms (SNPs) from blood DNA. A total of 184 subjects (20.0%) were confirmed to have MPC, 59 (32.8%) had synchronous MPC, and 128 (69.6%) had head and neck cancer. Elderly EC patients have an increased risk of having gastrointestinal cancer (Odds ratio, OR[95% CI]=6.70 [1.49–30.19], p=0.013) and a reduced risk of developing HNC (OR[95% CI]=0.44 [0.24–0.81], p=0.008). MPC risk was also associated with betel nut chewing (OR[95% CI]=1.63, 1.14–2.32], p=0.008), the A allele of ALDH2:rs671 (p=0.074 and 0.030 for GA and AA, respectively), the CC genotype in CISH:rs2239751 (OR[95% CI]=1.99 [1.2–3.32], p=0.008), and the G allele of ERCC5:rs17655 (p=0.001 and 0.090 for GC and CC, respectively). ADH1B:rs1229984 also correlated with MPC risk (p=0.117). Patients carrying four risk SNPs had a 40-fold risk of MPC (OR[95% CI]=40.25 [6.77–239.50], p<0.001) and a 12.57-fold risk of developing second primary cancer after EC (OR[95% CI]=12.57 [1.14–138.8], p=0.039) compared to those without any risk SNPs. In conclusion, hereditary variations in ALDH2, CISH, ERCC5, and ADH1B have great potential in predicting the incidence of MPC in EC patients. An extensive cancer screening program during clinical follow-up would be beneficial for patients with high MPC susceptibility.